Non-Medical Logistic Management at Syekh Yusuf Hospital of Gowa in 2021 - Momen Amalia; Andi Khaerul Musyawir (Lembaga Pengembangan Kinerja Dosen, 2022)
Good logistic management can have a big impact on service quality, therefore, logistic management needs to be monitored to know the weakness and strengths in its operatoonal implementation so that corrective can be taken for the implementation of logistic management which is not optimal. This studi aims to determine the implementation process of Non-Medical logistic management at the Syekh Yusuf Regional Public Hospital Gowa which focuses on the procurement process, storagr process, process of distribution, usage process, maintenance process, and process of deletion. This type of research used qualitative which aims to determine more deeply about the management of non-medical logistic at the Syekh Yusuf Hospital of Gowa. By conducting in-depth interviews and observations to informans.The research result from the procurement process indicators had not been categorized good, even though in essence the procurement of goods had used direct procurement and tender process. The strorage process had been categorized good. The distribution process had not been categorized as good because if the goods suddenly arrived when needed, the user had to wait because of logistic procurement once in a while a year. Then in the process of maintaining the goods has been effective. Management logistic on the elimination process can be categorized as good. Syekh Yusuf Hospital Gowa is expected to I,prove the procurement process at least every 6 month.